Les écoles congréganistes françaises de Smyrne à la fin du XIXe siècle, considérées par le chef de commerce Demetrius Georgiadès - Marina Vihou (Documents pour l'histoire du français langue étrangère, 2020)
The article examines the critique of the French congregational schools of Smyrna in the late 19th century, carried out by Demetrius Georgiades, a Smyrniot trade manager and, at the same time, a French-speaking journalist and author. Through the study of his journals and books, published in Paris at the dawn of the new century, we have been able to trace the origins of the skepticism that preoccupies the public opinion inside and outside of France, in connection with the confessional character of schools. Under the pretext of defending the French interests in these remote regions, Georgiades examines the role of congregational schools in the penetration of French commerce and the expansion of French language and civilization in Asia Minor. The questions of functioning and financing of these schools do not escape Georgiadès’s caustic pen either. To strengthen his arguments, Georgiades compares the education provided by French schools to that of Smyrna’s other foreign communities.